1990
DOI: 10.1002/eji.1830200435
|View full text |Cite
|
Sign up to set email alerts
|

The phosphorylation of the CD3 γ chain of T lymphocytes is modulated by β‐endorphin

Abstract: The neuropeptide beta-endorphin can modulate the response of T and B cells to mitogenic or antigenic stimulation. In the present report we describe a novel mechanism by which beta-endorphin can interfere with T cell activation. It is shown here that beta-endorphin can modulate the phorbol ester-induced phosphorylation of the gamma chain of the CD3 complex. The effect of beta-endorphin is dose dependent and appears to be mediated via interaction of beta-endorphin with an opiate receptor on lymphocytes. Evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…We show in fact that naloxone, removing the BE tone, accelerates graft rejection, but also that this effect is present only when the administration of the opiate receptor antagonist starts at the time of grafting, but not at a later time. The latter observation is consistent with the finding of Kavelaars et al [23], who demonstrated that opioid peptides modulate the phosphorylation of the CD3 g-chain of T cell antigen receptor function, i.e. the early activation of transduction pathways to the biological effect.…”
Section: Discussionsupporting
confidence: 92%
“…We show in fact that naloxone, removing the BE tone, accelerates graft rejection, but also that this effect is present only when the administration of the opiate receptor antagonist starts at the time of grafting, but not at a later time. The latter observation is consistent with the finding of Kavelaars et al [23], who demonstrated that opioid peptides modulate the phosphorylation of the CD3 g-chain of T cell antigen receptor function, i.e. the early activation of transduction pathways to the biological effect.…”
Section: Discussionsupporting
confidence: 92%
“…The hormonal regulation of assembly and disassembly of vimentin is known to be mediated via changes in phosphorylation of cytoskeleton elements (Browning & Sanders 1981, Marano et al 1989. In relation to our data on alterated of CD3 expression we have shown that y?-endorphin can modulate the phorbol ester-induced phosphorylation of the y-chain of the CD3 complex (Kavelaars et al 1990e). ^-endorphin can either enhance or inhibit the phosphorylation of the CD3 y-chain depending on the concentration of the pjeptide.…”
Section: Effect Of ^-Endorphin On Immune Responsivenesssupporting
confidence: 72%
“…To answer the question whether the emotion induction influences the functional activity of the cell via the modulation of membrane determinants such as CD3 (45) and/or via influencing directly cellular metabolism, the proliferative response of lymphocytes after stimulation with the protein kinase C stimulator phorboldibutyrate (PdB) in combination with the calcium ionophore ionomycin (iono) was tested. The above mentioned mitogens activate cells via triggering of cell surface determinants such as CD3 and CD2.…”
Section: W Cerritsen Et Almentioning
confidence: 99%